Howard Watkins and Christine Watkins Dressed Up for Barristers' Benefit Ball - Watkins, Howard::::::::: (1989)
Howard Watkins and Christine Watkins dressed up for BBB; Robin Watkins arms out and Adam Watkins In front of home and white Cressida ready to go to Fresno County Bar Association's BBB